RESPON TANAMAN KACANG TANAH (Arachis hypogea L.) TERHADAP PEMBERIAN PUPUK FOSFOR DAN ASAM TRIIODOBENZOAT - Innka Yasinta; Aslim Rasyad; Islan Islan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Triiodobenzoic acid (TIBA) is a plant growth regulator that may accelerate the change of vegetative growth into reproductive growth by modifiying the ratio of hormones that already exist. The purpose of this study was to determine the effect of TIBA and phosphorous fertilizer on peanut (Arachis hypogea L.). This study was conducted using a split plot design with three replications. The main plot was three levels of TIBA concentration; ie, 0 ppm, 50 ppm and 75 ppm. Subplot was four levels of phousphorous fertilizer; ie, 0 kg, 11,5 kg, 23 kg and 34,5 kg of  P2O5. Parameters measured were plant height, flowering age, number of primary branches, dry weight of plants at 28 days after planting, dry weight of plant at 35days after planting, plant growth rate, harvest index, pods dry weight per plot and seed weight per plot.The results showed that TIBA significantly affected pods dry weight and seed weight per plot, but not significantly affect plant height, flowering age, number of main branches, dry weight of plants at 28 days after planting, dry weight of plants at 35 days after planting, plant growth rate, and harvest index. Application of phosphorous fertilizer only affected harvest index, pod dry weight and seed weight per plot. TIBA and phosphorous interaction affected pod dry weight and seed weight per plot. Application of P2O5  fertilizer 34,5 kg per ha and TIBA with concentration of 75 ppm resulted higher pod dry weight and seed dry weight per area than other treatments. Keywords:Triiodobenzoic Acid, peanuts, phosphorous, plant height, seed weight.